Acanthopanax Senticosus Saponins induced tolerance to ischemia and its possible molecular mechanism in PC12 cells - Chen, Jian (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2007)
OBJECTIVE: To study the tolerance to ischemia induced by Acanthopanax Senticosus Saponins (ASE) in PC12 cells and the involved mechanism